Cultivo en suspensión de Mytella guyanensis (Bivalvia:Mytilidae) en Isla Chira, Costa Rica: implicaciones ambientales y biológicas. (Repertorio Científico, 2020)
In Costa Rica, the mariculture perspective has been increasing in the last decade as a strategy to mitigate social, environmental and economic conflicts within coastal communities, due to the misuse of marine resources from the locals. Diversifying the commercial offer and addressing a sustainable use of seafood in Isla Chira are the aims of this activity. Were to evaluate the growth, mortality rate and their relationship with environmental factors and conditions of the Mytella guyanensis suspended – culture broth. Monthly recording of the main environmental parameters of the culture broth took place during six months in addition to the biometric analysis of 300 individuals from the cultivated population in order to determine the appropriate commercial size. The mortality rate estimation was carried out using 60 baskets of organisms. The general environmental factor are suitable for the growing of the inoculated mussels. b) The average mussel’s mortality rate was 13 ± 4,5%; c) mussel growth in baskets is greater than the growth in natural banks and finally d) M. guyanensis reaches a suitable size for commercialization and consumption from the fifth month of cultivation (≥ 40 mm in length). We failed to stablish a correlation among the physicochemical parameters from the environment and the mortality rate recorded for harvested mussels (P